Airport competition within the Scottish lowlands region. (March 2020) - Pagliari, Romano; Graham, Anne
Abstract: The aim of this paper is to undertake an assessment of airport competition within the Scottish Lowlands region, which has experienced significant variations in economic development, and to examine whether competitive forces have been strengthening or weakening in recent years. This region covers the airports of Edinburgh, Glasgow and Prestwick in the last twelve years they have all experienced changes in ownership. BAA which had, for many years, operated both Edinburgh and Glasgow airports, sold the former to GIP in 2012 whilst in 2013 the Scottish Government purchased the privately-owned Prestwick. During this period there were also significant changes in airline network strategies. In order to assess the competitive pressures facing these airports, three key areas are considered, namely: aeronautical charging policy, the service quality provided and traffic development. The analysis shows that since ownership separation, competition has intensified between Edinburgh and Glasgow, whilst Prestwick airport, which benefitted from Ryanair expansion in the 1990s, is now a significantly diminished competitive proposition in the Scottish Lowland market. This has implications not only for airport policy and economic regulation but also for broader economic well-being in this region.